Driven to near‐experimental accuracy by refinement via molecular dynamics simulations. Issue 12 (24th June 2019) - Heo, Lim; Arbour, Collin F.; Feig, Michael
Abstract: Protein model refinement has been an essential part of successful protein structure prediction. Molecular dynamics simulation‐based refinement methods have shown consistent improvement of protein models. There had been progress in the extent of refinement for a few years since the idea of ensemble averaging of sampled conformations emerged. There was little progress in CASP12 because conformational sampling was not sufficiently diverse due to harmonic restraints. During CASP13, a new refinement method was tested that achieved significant improvements over CASP12. The new method intended to address previous bottlenecks in the refinement problem by introducing new features. Flat‐bottom harmonic restraints replaced harmonic restraints, sampling was performed iteratively, and a new scoring function and selection criteria were used. The new protocol expanded conformational sampling at reduced computational costs. In addition to overall improvements, some models were refined significantly to near‐experimental accuracy.